2001
DOI: 10.1046/j.1365-2249.2001.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated cytokine network and defective Th1 immune response in multiple myeloma

Abstract: SUMMARYIntracellular cytokine production by peripheral blood mononuclear cells (PBMC) was analysed in 51 patients with multiple myeloma (MM), 22 with monoclonal gammopathy of undetermined significance (MGUS) and 20 healthy subjects, as a parameter of immunological dysfunction in MM. An increased proportion of T cells and HLA-DR 1 cells producing IL-6 was observed in MM patients with active disease (at diagnosis and relapsing) compared with patients in remission and with MGUS, whereas no difference of IFN-g 1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 47 publications
(49 reference statements)
3
56
0
1
Order By: Relevance
“…27 In agreement with all these observations a defective IFN-␥ secretion by T cells was observed in MM patients. 28 The decrease in IFN-␥ levels observed in our cocultures could be due to the production of immunosuppressive factors by myeloma cells such as transforming growth factor ␤ (TGF-␤). It has been demonstrated that TGF-␤ from MM cells inhibits proliferation and IL-2 responsiveness in T lymphocytes, 29 and it is known that TGF-␤ suppresses IFN-␥ production in human T lymphocytes.…”
Section: Discussionmentioning
confidence: 90%
“…27 In agreement with all these observations a defective IFN-␥ secretion by T cells was observed in MM patients. 28 The decrease in IFN-␥ levels observed in our cocultures could be due to the production of immunosuppressive factors by myeloma cells such as transforming growth factor ␤ (TGF-␤). It has been demonstrated that TGF-␤ from MM cells inhibits proliferation and IL-2 responsiveness in T lymphocytes, 29 and it is known that TGF-␤ suppresses IFN-␥ production in human T lymphocytes.…”
Section: Discussionmentioning
confidence: 90%
“…34,35 This cytokine counterbalances the Th-2 polarizing activity of GM-CSF and restores the intrinsically defective Th-1 cytokine network of MM patients. 36 The TCR repertoire is determined by genetic and environmental factors, and is dynamically influenced by immune responses. Determination of the clonality and reciprocal usage of BV gene segments has shown that the TCR repertoire is severely disrupted in MM patients after high-dose chemotherapy and PBPC infusion.…”
Section: Idiotype Vaccination In Human Myelomamentioning
confidence: 99%
“…The corresponding myelomatous bone marrow is significantly altered due to factors aberrantly expressed by myeloma cells, those that are already expressed by normal plasma cells but present in higher abundance, and such expressed by a variety of cells of the (changing) bone marrow microenvironment (6)(7)(8)(10)(11)(12). One of the most prominent effects, thereof, is the induction of immunosuppression (13) visible in dysfunctional dendritic cells (DC) and diminished T-cell activation (13,14).…”
Section: Introductionmentioning
confidence: 99%